Alignment‐inducement property of physicochemically reconstructed EVA layer via plasma ion‐beam treatment for liquid crystal system. (12th December 2022) - Lee, Dong Wook; Kim, Dong Hyun; Oh, Jin Young; Yang, Da Bin; Won, Jonghoon; In Jang, Jong; Jeong, Hae‐Chang; Seo, Dae‐Shik
Abstract : Uniform and homogeneous liquid crystal (LC) alignment on a poly(ethylene‐co‐vinyl acetate) (EVA) layer subject to plasma ion‐beam (IB) treatment is confirmed. The layer molecular concentrations are controlled to 2, 4, and 6 wt%. Scanning electron microscopy exhibits a wrinkle pattern on the EVA surface that hinders LC alignment after IB treatment. However, X‐ray photoelectron spectroscopy shows chemical reconstruction on the surface; this induces strong van der Waals interactions with the LCs, which contribute to uniform LC alignment. The layer with higher molecular concentration is more heavily modified by IB treatment than that with low concentration, thereby achieving uniform LC alignment and overcoming topological disturbance. Contact angle analysis is used to verify that the surface energy increases via IB treatment; the uniform and homogeneous LC alignment is also confirmed by polarized optical microscopy and pretilt angle analysis. The EVA layer shows good optical transmittance and fine electro‐optical performances in terms of the switching and operating properties. Therefore, the plasma IB treatment is an effective method of deriving the surface characteristics of various polymeric materials for LC alignment, and the IB‐treated EVA layer has potential for application to LC systems.